ECLAMPSIA AND ITS ASSOCIATION WITH EXTERNAL FACTORS - Halimi, Surraya; Halimi, Syed Muhammad Ashhad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Eclampsia remains a leading cause of maternal and perinatal mortality and morbidity. Primigravida are at higher risk of convulsions and antepartum convulsions are more dangerous than those beginning after delivery. This study was carried out to evaluate the epidemiological aspects of patients presenting with eclampsia in the catchment area of Saidu Teaching Hospital Swat. Methods: This descriptive non-interventional study was carried out in the Department of Obstetrics and Gynaecology, Saidu Teaching Hospital Swat from 1st January 2007 to 31st December 2009. Nonprobability consecutive sampling method was used. All patients of eclampsia were included in the study. The diagnosis was based on history and confirmed on clinical findings. Inclusion criteria were patients with hypertension, proteinuria and history of fits during pregnancy; labour and peurperium within 7 days of delivery. Exclusion criteria were history of fits other than eclampsia. Results: A total of 23,000 admissions were made in the labour ward during the study period. Out of them 108 cases (0.46%) were of eclampsia, 85 were primigravidae with no previous history of hypertension and 23 were multigravidae with previous history of hypertension. The seasonal frequency of cases was 34.25% in winters, 17.59% in autumn, 21.29% in summers and 26.85% in spring. The incidence of eclampsia was 79.62% in primigravida, and 75% in the age group 14-19 years. The prevalence was high (82.40%) in poor socioeconomic class patients. Conclusion: Eclampsia is a common pregnancy associated disorder in this part of the country especially in primigravida and teenagers. The disorder is common in low socioeconomic class. The most important aspect of its management is prevention by proper antenatal check-up, availability of health facilities and prompt referral to tertiary care hospital. Keywords: Eclampsia, Pregnancy, primigravida, seasonal variation